Information causes – triggers and resonant discourses of the national media space: possibilities of sociological analysis - Belski, Alexander M. (Journal of the Belarusian State University. Sociology, 2020)
The article indicates the relevance of the study of conditionally neutral informational triggers in the context of the discussions they produce in the modern media space. The authorʼs methodology of highlighting resonant discourses of the countryʼs leading information resources in the context of actual trigger events of the national information field is demonstrated in order to analyse their interpretive environment for the formation of semantic meanings, distorting the meaning of the original informational occasion and provoking destructive social activity. Based on the presented case, proposals are made for correcting the direction of conflict discourses.
Keywords: trigger event; media space; discourse; intertextuality; interdiscursiveness; conflict discourse; symbolic capital; informational impact